Clinico-pathological Analysis of Malignant Eyelid and Adnexal Tumors Presenting to a Tertiary Eye Hospital Of Eastern Nepal - Kafle, Prerna Arjyal; Hamal, Diwa; Sahu, Sabin; Poudyal, Priza; Kafle, Santosh Upadhyaya (Birat Journal of Health Sciences, 2020)
Introduction: Eye lid and adnexal tumours are one of the major problems we see in the oculoplastic department. Malignant eye lid tumours are rare in comparison to benign and diversity in its clinical presentation makes it difficult to diagnose earlier. Eyelid malignancies can mimic a host of benign neoplasms and other less aggressive neoplastic or non-neoplastic inflammatory conditions and need differentiation before definitive therapy is planned. Out of 90% of all skin cancer occurring in head and neck region 10% occurs in the eyelid. A histopathological study confirms the diagnosis that can be correlated with patient history and other clinical data. Objectives: To study the clinicopathological correlation and its outcome in patients with malignant eyelid and adnexal tumours presenting at Biratnagar eye hospital. Methodology: Details of the cases of histopathologically proven malignant eyelid and adnexal tumours presenting to the department of oculoplasty from July 2016 to August 2019 were recorded. The duration of disease, presenting symptoms, risk factors, demographic data, clinicopathological correlation with its accuracy and mode of treatment were analyzed using SPSS 17. Results: Out of total 28 patients, male were 53.6% and female were 46.4%. The mean age of presentation was 60.5±11.8 years. 53.6% tumors were located in upper lid, 39.9% were located in lower lid and 7.1 % were located in medial canthus. Basal cell carcinoma and sebaceous gland carcinoma were the most common type of malignancies (35.7% each) followed by 28.6% of squamous cell carcinoma of eyelid. The clinicopathological correlation revealed 75% of clinical accuracy. Different types of reconstructions were done according to the size and site of the defect. Modified Hughes procedure for lower eyelid defect was the most common procedure performed (32.1%), followed by 14.3% Cutler beard, 28.6% Cutler beard with post auricular cartilage graft, 10.7% Glabellar flap rotation 7.1% had combined procedure and 4.3% direct closure . Conclusion: Sebaceous cell carcinoma and Basal cell carcinoma were the most common malignant tumors followed by squamous cell carcinoma. The upper lid was the most common site for such malignancy. Histopathological examination was useful for the establishment of complete and accurate diagnosis, which led to further management and follow up protocol for malignant eyelid tumours.